2017
DOI: 10.1007/s10549-017-4155-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical tumor stage is the most important predictor of pathological complete response rate after neoadjuvant chemotherapy in breast cancer patients

Abstract: BackgroundPathological complete response (pCR) is the ultimate response in breast cancer patients treated with neoadjuvant chemotherapy (NCT). It might be a surrogate outcome for disease-free survival (DFS) and overall survival (OS). We studied the effect of clinical tumor stage (cT-stage) on tumor pCR and the effect of pCR per cT-stage on 5-year OS and DFS.MethodsUsing the Netherlands Cancer Registry, all primary invasive breast cancer patients treated with NCT from 2005 until 2008 were identified. Univariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 23 publications
(25 reference statements)
9
62
1
2
Order By: Relevance
“…Although the TNBC-RPS showed good prediction power in TNBC patients, we were concerned that tumor stage or grade might have confounded these findings; it has been reported that TNBC patients with a more advanced tumor stage or grade tend to have better response to NCT. 59 To evaluate this, we first examined the predictive ability of the TNBC-RPS in the validation metadata for each tumor stage. By calculating the TNBC-RPS for each individual stage in both pCR and RD patients (Table S9), we found that pCR patients had significantly higher RPS than RD patients (P = .007, Stage I; P = 9e-6, Stage II; P = .004, Stage III; P = 1e-6, Stage IV; Table S9).…”
Section: The Tnbc-rps Predicts Nct Response In Each Clinical Stagementioning
confidence: 99%
“…Although the TNBC-RPS showed good prediction power in TNBC patients, we were concerned that tumor stage or grade might have confounded these findings; it has been reported that TNBC patients with a more advanced tumor stage or grade tend to have better response to NCT. 59 To evaluate this, we first examined the predictive ability of the TNBC-RPS in the validation metadata for each tumor stage. By calculating the TNBC-RPS for each individual stage in both pCR and RD patients (Table S9), we found that pCR patients had significantly higher RPS than RD patients (P = .007, Stage I; P = 9e-6, Stage II; P = .004, Stage III; P = 1e-6, Stage IV; Table S9).…”
Section: The Tnbc-rps Predicts Nct Response In Each Clinical Stagementioning
confidence: 99%
“…Among other means of predicting response to NAT, such as using tumor stage and receptor status 19 , features extracted from pre-treatment MRI have shown promise for this purpose 8,18,2028 . Using MRI could provide a fast and noninvasive way to further stratify patients at no additional cost to patients who already require MRI as part of a standard preoperative workup for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Individual responses to NAC vary widely, depending on molecular subtype ( i.e. estrogen receptor (ER) negative and human epidermal growth factor receptor 2 (HER2) positive tumors respond better) [ 2 ], tumor size [ 3 ] and treatment regimen [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%